Pengaruh Analisis Laporan Keuangan Terhadap Keputusan Investasi - Ryanni Sarah Simangunsong; Audira Ginting; Ardi Lumban Tobing; Hamonangan Siallagan (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the influence of financial statements on investment decision-making by investors in the capital market. Financial statements are the main source of information used by investors to assess company performance, measure risk, and predict future profits. Through the analysis of financial ratios such as liquidity, profitability, leverage, and activity, this study explores how much influence financial statements have in influencing investment decisions. The results of the study show that financial statements that show strong company performance, especially in terms of profitability and solvency, have a positive correlation with investment interest. In addition, transparent and informative financial statements also strengthen investor confidence in making decisions. These findings support that financial statement analysis plays a significant role in investment decisions and is a very important tool for investors in managing risk and planning their portfolios.